2012
DOI: 10.5455/medarh.2012.66.198-200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Nigella Sativa Seeds for the Treatment of Hyperlipidemia: a Randomized, Placebo Controlled Clinical Trial

Abstract: According to the results of our present study it seems that N. sativa may have some beneficial therapeutic effects in the treatment of hyperlipidemia. However, further investigations with a larger sample size are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 14 publications
4
59
0
Order By: Relevance
“…The results showed that a combination of NS supplementation with aerobic training significantly improves lipid profile by decreasing plasma TC, LDL-C, and TG, and increasing HDL-C concentrations [60]. Results of a similar study that was performed on hyperglycemic subjects showed hypolipidemic effects of NS seed powder following 4 weeks of treatment [61]. In another study, NS seed powder and Allium Sativum were administrated as adjunct to simvastatin and could significantly improve lipid profile after 8 weeks of treatment in a randomized, double-blind, placebo-controlled trial [62].…”
Section: Clinical Studiesmentioning
confidence: 72%
“…The results showed that a combination of NS supplementation with aerobic training significantly improves lipid profile by decreasing plasma TC, LDL-C, and TG, and increasing HDL-C concentrations [60]. Results of a similar study that was performed on hyperglycemic subjects showed hypolipidemic effects of NS seed powder following 4 weeks of treatment [61]. In another study, NS seed powder and Allium Sativum were administrated as adjunct to simvastatin and could significantly improve lipid profile after 8 weeks of treatment in a randomized, double-blind, placebo-controlled trial [62].…”
Section: Clinical Studiesmentioning
confidence: 72%
“…A randomized, placebo controlled clinical trial proved that Nigella sativa has a significant decrease in the concentration of total cholesterol (4.78%), low density lipoprotein (7.6%) and Triglyceride (16.65%). This decrease was more significant for TG concentration (39). Other study showed that Nigella sativa reduced fasting blood sugar (40).…”
Section: Discussionmentioning
confidence: 96%
“…The conventional diet was recommended by dietitians on specific forms and the diet of Persian Medicine was accurately determined on the basis of Persian Traditional Medicine. It should be noted that the calorie diet was similar in the three groups, in which foods with hot and dry temperament recommended by Persian Medicine sources (39) were selected from the main and alternative lists of conventional diet, and foods with cold and wet temperament, the consumption of which was forbidden to obese people in the sources of Persian Medicine (9,29) were removed from the main and alternative lists of conventional diet. Participants in this study were on a low-calorie diet designed to reduce the initial weight of 0.5 to 1 kg/week.…”
Section: Interventionmentioning
confidence: 99%
“…The seeds of N. sativa have metabolites that have anti-oxidant activities. These beneficial effects can help in the reduction of atherosclerosis (Sabzghabaee et al, 2012).…”
Section: Nigella Sativamentioning
confidence: 99%